2023
DOI: 10.1007/s12350-022-03108-z
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-guided vs routine non-culprit vessel angioplasty for patients with ST segment elevation myocardial infarction and multi-vessel disease: the IAEA SPECT STEMI trial

Abstract: Background In patients with multi-vessel disease presenting with ST elevation myocardial infarction (STEMI), the efficacy and safety of ischemia-guided, vs routine non-culprit vessel angioplasty has not been adequately studied. Methods We conducted an international, randomized, non-inferiority trial comparing ischemia-guided non-culprit vessel angioplasty to routine non-culprit vessel angioplasty, following primary PCI for STEMI. The primary outcome was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Moreover, previous studies demonstrated that the changes in perfusion parameters, obtained early and 6 months after acute myocardial infarction, have a great prognostic impact in predicting long-term outcome. 29 In Karthikeyan et al 28 investigation, including a mean time between the two imaging studies of 16.5 months, no data on subsequent follow-up are reported. Moreover, despite the amount of ischemia at imaging after revascularization was comparable between routine non-culprit PCI vs. image guided PCI, the authors suggest that selective non-culprit PCI following STEMI offers the potential for cost-savings and may be particularly relevant to low-resource settings.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Moreover, previous studies demonstrated that the changes in perfusion parameters, obtained early and 6 months after acute myocardial infarction, have a great prognostic impact in predicting long-term outcome. 29 In Karthikeyan et al 28 investigation, including a mean time between the two imaging studies of 16.5 months, no data on subsequent follow-up are reported. Moreover, despite the amount of ischemia at imaging after revascularization was comparable between routine non-culprit PCI vs. image guided PCI, the authors suggest that selective non-culprit PCI following STEMI offers the potential for cost-savings and may be particularly relevant to low-resource settings.…”
mentioning
confidence: 97%
“…In the current issue of the Journal, Karthikeyan et al 28 conducted an international, randomized, non-inferiority trial comparing ischemia-guided non-culprit vessel angioplasty to routine non-culprit vessel angioplasty, following primary PCI for STEMI (IAEA SPECT STEMI trial). They hypothesized that a strategy of systematic noninvasive assessment of inducible ischemia to guide decisions regarding non-culprit PCI, will be noninferior to routine non-culprit PCI, in reducing ischemia burden.…”
mentioning
confidence: 99%
See 3 more Smart Citations